Improving Local Government Financial Performance: The Role of Management, Transparency, and Accountability - Zein, M. Harry Mulya; Septiani, Sisca (Journal of Posthumanism, 2025)
This study aims to analyze the influence of local financial management and transparency on local financial performance, considering the mediating role of accountability. This study uses a quantitative approach with an explanatory survey design, involving all Regional Work Units in one district/city in West Java as respondents. Primary data were collected through structured questionnaires and analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that accountability significantly influences local government financial performance. Transparency also significantly influences accountability, but not directly on performance. Conversely, local government financial management does not show a significant influence, either directly or indirectly, through accountability. These findings confirm that accountability is an important mediator in strengthening the influence of transparency on local government financial performance. This study offers theoretical contributions by highlighting the role of accountability as a strategic mediating element in public governance and practical implications that local government financial reforms should be directed toward strengthening accountability systems, rather than merely focusing on procedural efficiency.